The Impact of Social Media Marketing Activities on Brand Image and Purchase Intention: The Mediating Role of Brand Awareness in the Context of Digital Consumers in Indonesia: Dampak Aktivitas Pemasaran Media Sosial terhadap Citra Merek dan Niat Beli: Peran Mediasi Kesadaran Merek dalam Konteks Konsumen Digital di Indonesia - Mohamat Basori; Arif Nugroho; Arif Hidayat (OGZ Research & Publishing, 2026)
Abstract: The digital marketing landscape in Indonesia has undergone rapid transformation, driven by the massive penetration of social media, particularly among younger generations. This study aims to examine the influence of Social Media Marketing Activities (SMMAs) on brand image and purchase intention, with brand awareness acting as a mediating variable. Employing a quantitative approach, a survey was conducted with 464 respondents in Indonesia who are active social media users and have experience with online purchases. Data were analyzed using Covariance-Based Structural Equation Modeling (CB-SEM) with LISREL software. The results indicate that SMMA has a positive and significant effect on brand awareness (β=0.809, p=0.000), brand image (β=0.603, p=0.000), and purchase intention (β=0.427, p=0.000). Brand awareness also demonstrated a positive influence on brand image (β=0.312, p=0.002) and purchase intention (β=0.463, p=0.000). A key finding reveals that brand awareness fully mediates the effect of SMMA on both brand image and purchase intention. This research contributes theoretically by extending the application of the Theory of Planned Behavior and the Hierarchy of Effects Model within Indonesia's digital economy context. For practical implications, marketers are advised to design SMMAs that are entertaining, trendy, and personalized to build strong brand awareness and image, which ultimately fosters purchase intention. Keywords: Social Media Marketing Activities, Brand Awareness, Brand Image, Purchase Intention, Indonesian Digital Consumers